PENGARUH LITERASI KEUANGAN, GAYA HIDUP DAN UANG ELEKTRONIK TERHADAP PERILAKU KONSUMTIF (STUDI KASUS DI SMK JAKARTA 1 - Feby Krismayanti; Muhammad ichwan Hamzah; Burhan (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2023)
This study aims to determine the effect of financial literacy, lifestyle and electronic money on consumtive behavior (case study of SMK Jakarta 1) either partially or simultaneously. This study uses a quantitative approach. The sample this study was 100 students at SMK Jakarta 1 by using non-probability sampling and simple random sampling. The research instrument used a questionnaire and the analysis used multiple regression analysis. The results of this study indicate that (1) financial literacy has a positive and significant effect on consumtive behavior (2) lifestyle has a a positive and significant effect on consumtive behavior (3) electronic money no has a and n significant no effect on consumtive behavior (4) financial literacy (X1 ), lifestyle (X2) has a effect simultaneous on consumptive behavior while electronic money (X3) has no effect on consumptive behavior (Y) in the case Study of SMK Jakarta 1.